Empowerment of Housewives and Marketing Strategies in the Development of Various Citrus Fruit Processed Businesses in Catur Village, Kintamani, Bali - Ni Luh Putu Putri Setianingsih; I Ketut Selamet; I Wayan Sudiarta; I Wayan Wesna Astara (PT FORMOSA CENDEKIA GLOBAL, 2023)
The activities of the Assisted Village Empowerment Program, which are carried out in Catur Village, Kintamani, and Bangli-Bali, aim to increase the knowledge and skills of groups of housewives in managing the results of citrus fruit products into various processed citrus fruits that have economic value. The Housewives Group has become a leader in citrus fruit management at the household level. The methods used include observation, counseling, education, and direct practice. Based on the results, 100% of the Housewives Group can use tools for the product manufacturing process to produce various processed citrus fruits that have economic value and quality. The group of housewives in Catur Village, after receiving socialization and training, is committed to producing citrus fruits and making various processed citrus fruits into products that have economic value and quality.